Patient-Controlled Thoracic Epidural Infusion With Ropivacaine 0.375% Provides Comparable Pain Relief as Bupivacaine 0.125% Plus Sufentanil After Major Abdominal Gynecologic Tumor Surgery. Issue 4 (1st July 2002) - Gottschalk, André; Freitag, Marc; Burmeister, Marc-Alexander; Becker, Cornelia; Horn, Ernst-Peter; Standl, Thomas
Abstract : Background and Objectives: We tested the hypothesis that an opioid-free local anesthetic alone is able to provide comparable analgesia to the opioid supplemented epidural application of local anesthetics using thoracic epidural catheters after major abdominal surgery. Methods: In a prospective, randomized, and double-blind study, we have compared the analgesic efficacy and side effects of ropivacaine 0.375% (group R) versus bupivacaine 0.125% in combination with sufentanil 0.5 μg/mL −1 (group B/S) via a thoracic epidural catheter for a duration of 96 hours after major abdominal surgery in 30 gynecologic tumor patients. Piritramide was given for breakthrough pain. Assessments were performed every 12 hours after start of the epidural infusion using continuous (first 24 hours) and patient-controlled epidural analgesia (PCEA) (24 to 96 hours). Results: No differences were seen in demographic and perioperative data. Dynamic pain scores (visual analog scale [VAS] values) were comparable between groups during mobilization (group R v group B/S: 24 hours: 40 ± 30 v 36 ± 14, P = .9; 48 hours: 46 ± 33 v 42 ± 25, P = .93; 72 hours: 42 ± 24 v 48 ± 26, P = .78; 96 hours: 42 ± 25 v 29 ± 28, P = .49) and on coughing during the whole study period. Hemodynamics, intensity of motor block (Bromage scale), and side effects like nausea, vomiting, pruritus, and bladder disfunction also did not differ between groups. Conclusion: The present study shows that thoracic epidural infusion of ropivacaine 0.375% provides comparable pain relief and incidence of side effects after major abdominal gynecologic surgery as bupivacaine 0.125% in combination with 0.5 μg/mL −1 sufentanil and may therefore represent an alternative in epidural pain management.